The trend of groundwater recharge in the secondary perched reaches of the Yellow River in the past 50 years - Zhang, Min; Ping, Jianhua; Mei, Xuemei; Leng, Wei; Li, He; Zhao, Jichang; Liu, Jiaqi (Frontiers in Environmental Science, 2023)
Abstract：Precipitation infiltrates into the soil or river and then percolates downward through the deeper mineral soil to the groundwater. Understanding the interactions between surface water and groundwater in the river ecosystem is crucial for supporting decision-making in eco-construction and the efficient use of water resources. In our study, the secondary perched reach of the lower Yellow River was taken as the research area. The trend analysis and correlation relationship were evaluated using the M-K significance test and grey correlation, further the groundwater recharge was quantified by Darcy 's law and water balance method based on 50 years hydrological data. The results showed that: (1) From 1972 to 2020, the runoff and water level of Huayuankou hydrological station and Jiahetan hydrological station showed a significant downward trend. (2) The calculation of grey correlation degree method shows that groundwater level is mainly affected by the recharge of the Yellow rRiver water. The river water level and groundwater level shows a significant downward trend using M-K significance test. (3) The unit width recharge of the secondary perched river to the groundwater in the dry year were calculated to be 566.79 m 3 /m• d and 374.13 m 3 /m• d, using Darcy 's law and water balance method, respectively, indicating that the results of two methods are basically the same. Our finding can provide the support for regulation and storage capacity of groundwater and sustainable management of water resources in ecosystem.